2018
DOI: 10.1136/bmjopen-2018-021924
|View full text |Cite
|
Sign up to set email alerts
|

Study protocol for a single-centre, prospective, non-blinded, randomised, 12-month, parallel-group superiority study to compare the efficacy of pharmacist intervention versus usual care for elderly patients hospitalised in orthopaedic wards

Abstract: IntroductionGiven that polypharmacy and potentially inappropriate prescribing are common in elderly orthopaedic patients, pharmacist interventions to improve medication practices among this population are important. However, past studies have reported mixed results regarding the effectiveness of pharmacist-led interventions in inpatient elderly care. Furthermore, few randomised controlled trials have evaluated patient-relevant outcomes as a primary endpoint. Therefore, we will evaluate whether a pharmacist-led… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Optimizing perioperative drug therapy such as anticoagulation management, anti‐infective treatment and postoperative pain control can directly improve the patient's postoperative situation like postoperative venous thromboembolism (VTE), postoperative infection, hospital stay and readmission rate. Published studies on the role of clinical pharmacists in multidisciplinary teams have shown that clinical pharmacists have a positive influence on orthopaedic surgery care, including optimization of VTE prophylaxis administration, related quality indicators, 6,7 surgical site infection prevention, 8 pain management and opioid use 9,10 . The implementation of a comprehensive clinical pharmacy service, from an institution providing TJA procedures in the United States, was associated with improved institutional rates of postoperative readmissions and complications, patient understanding and satisfaction 11 …”
Section: What Is Known and Objectivementioning
confidence: 99%
“…Optimizing perioperative drug therapy such as anticoagulation management, anti‐infective treatment and postoperative pain control can directly improve the patient's postoperative situation like postoperative venous thromboembolism (VTE), postoperative infection, hospital stay and readmission rate. Published studies on the role of clinical pharmacists in multidisciplinary teams have shown that clinical pharmacists have a positive influence on orthopaedic surgery care, including optimization of VTE prophylaxis administration, related quality indicators, 6,7 surgical site infection prevention, 8 pain management and opioid use 9,10 . The implementation of a comprehensive clinical pharmacy service, from an institution providing TJA procedures in the United States, was associated with improved institutional rates of postoperative readmissions and complications, patient understanding and satisfaction 11 …”
Section: What Is Known and Objectivementioning
confidence: 99%
“…The treatment of frail orthopaedic patients is a difficult task for any single profession, and several studies have demonstrated an improvement in their care through a multidisciplinary approach . Specifically focusing on orthopaedic patients' medications, a clinical pharmacy service is regarded as an extension of this approach.…”
Section: What Is Known and Objectivementioning
confidence: 99%